THE IMPACT OF TIKTOK TOURISM CONTENT ENGAGEMENT ON VISITING INTENTION: A SURVEY OF @JKTGO FOLLOWERS - Garcia Krisnando Nathanael; Cinta Arthamevia Nasikah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
TikTok has become an influential platform for discovering tourism recommendations in Indonesia, particularly through high-engagement accounts such as @jktgo. Despite its engagement rate of 4.27%, tourist visits to Jakarta have declined, indicating a potential gap between online engagement and behavioral intention. This study investigates the effect of engagement with TikTok tourism promotional content on followers’ intention to visit Jakarta. Guided by the Elaboration Likelihood Model (ELM), this research employed a quantitative explanatory design and surveyed 400 @jktgo followers selected using purposive sampling. The study analyzes data using validity and reliability tests, normality testing, correlation analysis, simple linear regression, and the coefficient of determination. The results show that content engagement significantly influences visiting intention, with an R Square value of 0.711, showing that 71.1% of the variance in visiting intention is explained by engagement. The findings confirm that TikTok engagement can shape behavioral intention via both central and peripheral processing routes. This study highlights the strategic role of TikTok as a tourism promotion tool and offers insights for stakeholders to enhance digital tourism marketing initiatives.